(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
This article analyzes the relationship between emotional intelligence (EI) and the level of satisfaction with family life from a socio-psychological perspective. The study highlights the importance of empathy in family life quality, emotional regulation, communication culture, and interpersonal relationships. The results show that a high level of emotional intelligence is an important factor in increasing stability, positive climate, and satisfaction in family relationships.